Ekplorasi Budaya Pembelajaran Bahasa Arab di Sekolah Indonesia Makkah: Studi Etnografi - Luthfiah, Nadya Nadjwa; Wahyudin, Wahyudin; Sumiarni, Nanin (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2025)
This study aims to explore the culture of Arabic language learning at Sekolah Indonesia Makkah (SIM), with a research focus that includes an analysis of learning methods and strategies, the role of the school environment in shaping a learning culture, and the challenges faced by students and teachers. This study uses a qualitative approach with an ethnographic type. The ethnographic research cycle procedure is based on Spradley's theory, namely: project selection, posing questions, data collection, collecting research records, data analysis, and writing reports and data sources. Data sources are obtained from observations, interviews, and documentation, which are then analyzed using the Spradley model with domain and taxonomy analysis. The results of the study show that: 1) Arabic language learning at SIM combines interactive and traditional approaches and integrates technology such as Smart TV, Computer Lab, SIM TV Studio, and interactive learning applications. 2) Learning involves 4 maharat: al-kalam, al-qira'ah, al-kitabah, and al-istima'. 3) The school environment, including facilities and extracurricular activities such as the Arabic Club, 3S Habits (smile, greet, and say hello), memorizing the Qur'an, reciting prayers, and reviewing last week's material, plays an important role in forming a culture of learning Arabic. However, there are various challenges for students, such as difficulty in understanding Arabic grammar, differences in dialects, and variations in students' interests and motivations for learning. Likewise, for teachers, with differences in culture, language of instruction, language skills, learning styles, and motivations for learning between students, teachers are required to maximize their abilities in the learning process. This study provides insight into the culture of learning Arabic at SIM as an effort to support Indonesian education abroad. Abstrak Penelitian ini bertujuan untuk mengeksplorasi budaya pembelajaran bahasa Arab di Sekolah Indonesia Makkah (SIM) dengan fokus penelitian meliputi analisis metode dan strategi pembelajaran, peran lingkungan sekolah dalam membentuk budaya belajar, serta tantangan yang dihadapi siswa dan guru. Penelitian ini menggunakan pendekatan kualitatif dengan jenis etnografi. Prosedur siklus penelitian etnografi berdasarkan teori Spradley yaitu: pemilihan proyek, pengajuan pertanyaan, pengumpulan data, pengumpulan rekaman penelitian, analisis data, dan penulisan laporan dan sumber data. Sumber data diperoleh dari hasil observasi, wawancara dan dokumentasi yang kemudian dianalisis menggunakan model Spradley dengan analisis domain dan taksonomi. Hasil penelitian menunjukkan bahwa: 1) pembelajaran bahasa Arab di SIM menggabungkan pendekatan interaktif dan tradisional, serta mengintegrasikan teknologi seperti Smart TV, Lab Komputer, Studio SIM TV dan aplikasi pembelajaran interaktif. 2) Pembelajaran melibatkan 4 maharat: al-kalam, al-qira’ah, al-kitabah dan al-istima’. 3) Lingkungan sekolah, termasuk fasilitas dan ekstrakurikuler seperti Arabic Club, Pembiasaan 3S (senyum, sapa, dan salam), tahfidz Qur’an, membaca do’a dan mengulas materi pekan lalu berperan penting dalam membentuk budaya belajar bahasa Arab. Namun, terdapat berbagai tantangan pada siswa seperti kesulitan memahami tata bahasa Arab, perbedaan dialek, serta variasi minat dan motivasi belajar siswa. Begitupun pada guru, dengan adanya perbedaan budaya, bahasa pengantar siswa, kemampuan berbahasa, gaya belajar serta motivasi belajar antar siswa mengharuskan guru untuk memaksimalkan kemampuannya dalam proses pembelajaran. Studi ini memberikan wawasan tentang budaya belajar bahasa Arab di SIM sebagai upaya mendukung pendidikan Indonesia di luar negeri.